Growth optimization of mangrove Streptomyces for enhancement of actinorhodin production - Azizan, Nur Hafizah; Zainal Abidin, Zaima Azira; Sharif, Mohd. Faez; Zainuddin, Zarina; Khan Chowdhury, Ahmed Jalal (2021)
The family Streptomycetaceae, notably species in genus Streptomyces, have long been the subject of investigation due to their well-known ability to produce secondary metabolites. Even though thousands of secondary metabolites have been discovered from Streptomyces, less attention has been given in understanding the bioprospecting of the secondary metabolites in Streptomyces living in mangrove ecosystem. Therefore, the current study was designed to investigate the production of actinorhodin from mangrove Streptomyces which was grown in different parameters. Phylogenetic analysis showed that the Streptomyces sp. K2-11 belongs to Streptomyces prasinus strain NRRL B-12521 with 99.62% similarity. High-performance liquid chromatography analysis has detected the presence of actinorhodin compound in Streptomyces sp. k2-11. The compound showed inhibitory activity to Bacillus subtilis and no activity against Streptococcus aureus based on disc diffusion assay. Streptomyces sp. growth in SMMS media was recorded to be the highest (1.49 × 108 cfu/ mL) compared with SYE and R2 media. The production of actinorhodin was tested on three different parameters: incubation temperature, pH and glucose levels. The highest production of actinorhodin was recorded at 33°C (1.95 × 10–6 mol/L), pH 5 (7.1 × 10–6 mol/L) and 50% w/v glucose (9.56 × 10–6 mol/L) for 60 h of incubation. The present finding suggested that mangrove Streptomyces sp. K2-11 produced high yield of actinorhodin under extreme or stress condition.